Description of Leptus (Leptus) haitlingeri n. sp. (Trombidiformes: Erythraeidae), parasitising horse flies (Diptera: Tabanidae), and a key to the larvae of Leptus spp. in Brazil - de Castro Jacinavicius, Fernando; Bassini-Silva, Ricardo; Soares, João Fábio; Virginio, Flávia; Welbourn, Cal; Barros-Battesti, Darci Moraes [UNESP] (Springer Nature, 2019)
The genus Leptus Latreille, 1796 (Trombidiformes: Erythraeidae) is represented by more than 250 species worldwide, and the larval stages of these mites are ectoparasites of many arthropod orders. In Brazil, there are 12 species of Leptus, some of which have been reported parasitising representatives of the orders Opiliones, Araneae, Coleoptera, Heteroptera, Hymenoptera and Diptera. This paper describes Leptus (Leptus) haitlingeri n. sp. collected from horse flies (Diptera: Tabanidae) in the state of Sao Paulo, Brazil. The new species is distinguished from L. (L.) adaminae Haitlinger, 2004 and L. (L.) fozicus Haitlinger, 2004 by the presence of 4 branched setae on palptarsus (vs 2 branched setae). A key to the larvae of Leptus spp. in Brazil is provided.